Does addition of a diagnostic contrast-enhanced CT to a contemporaneous PET/CT provide incremental value in patients for restaging of colorectal carcinoma? - Kenneth S. K. Yap; Ojas H. Mehta; Wing Fai Eddie Lau; Tim Akhurst; Satish Warrier; Alexander Heriot; Rodney J. Hicks (European Journal of Hybrid Imaging, 2018)
Abstract Background Both constrast-enhanced computed tomography (ceCT) and 18F-Fluorodeoxyglucose positron emission tomography (PET) are widely used for evaluation of colorectal cancer. Not infrequently patients undergo both tests, increasing cost and radiation burden. Whether this combination provides useful incremental diagnostic information remains unclear. Our purpose was to determine whether the addition of ceCT to PET/CT results in an appropriate change in the N or M stage in patients with colorectal cancer. Methods This was a single centre, retrospective study in a tertiary referral hospital. Over 9 months, 74 consecutive patients with colorectal carcinoma were referred for PET with a recent ceCT scan and adequate follow-up were analysed. The N and M stage of each modality was compared. Management was determined according to institutional guidelines with incremental impact of ceCT results on management categorised as appropriate, inappropriate or unchanged, based on pathological results, clinical or imaging follow-up of discrepant findings. Results Of 74 patients, PET/CT and ceCT N and M stages were concordant in 56 patients (76%) but PET/CT and ceCT identified additional abnormalities in 9 cases each respectively. Of the 18 discordant cases, accepting the ceCT result would have appropriately changed management in only 2 patients and inappropriately in 1 with most management plans unchanged. When comparing PET/CT and ceCT, kappa agreement (95% confidence interval) for N and M stage was 0.58 (0.20–0.95) and 0.60(0.41–0.79) respectively reflecting moderate agreement. Conclusions Whole-body ceCT probably has limited management impact in colorectal cancer patients who are also undergoing PET/CT and therefore may possibly be omitted from routine use. Targeted regional MRI or ceCT should, however, be considered based on clinical suspicion or when high-resolution anatomical information is required for treatment planning.